The Delphi technique in ecology and biological conservation: applications and guidelines. Issue 9 (28th April 2015) - Mukherjee, Nibedita; Hugé, Jean; Sutherland, William J.; McNeill, Jeffrey; Van Opstal, Maarten; Dahdouh‐Guebas, Farid; Koedam, Nico; Anderson, Barbara
Summary Many areas of science, including conservation and environmental management, regularly require engaging stakeholders or experts to produce consensus or technical inputs. The Delphi technique is an iterative and anonymous participatory method used for gathering and evaluating such expert‐based knowledge. We outline the methodology of the Delphi technique and provide a taxonomy of its main variants. In addition, we refine the technique by providing suggestions to address common limitations (e.g. time consumption, attrition rate) in order to make the method more suitable for application in ecology and conservation. A comprehensive search for studies that have applied the Delphi technique in conservation and environmental management resulted in 36 papers. The Delphi technique has been applied to a range of issues, including developing decision support systems and predicting ecological impacts of climate change. The papers reviewed suggest that the Delphi technique is an efficient, inclusive, systematic and structured approach that can be used to address complex issues. A major strength compared to other group‐based techniques is the reduced influence of social pressures among respondents. The Delphi technique is relatively little used and seems undervalued. Given its wide range of possible applications, it could be applied more widely in evaluating evidence and providing expert judgments.